Southward Drift of Eastern Australian Hotspots in the Paleomagnetic Reference Frame Is Consistent With Global True Polar Wander Estimates - Hansma, Jeroen; Tohver, Eric (Frontiers in Earth Science, 2020)
Eastern Australian hotspots produce the longest continental tracks on Earth (>2000 km). These hotspots are generally assumed to be stationary with respect to one another, an observation reinforced by our analysis. If any motion between them occurred, it is within our 95% uncertainties of 370km of accumulated motion between hotspots. In contrast, motion between eastern Australian hotspots and the spin axis is indicated by changing paleolatitudes of hotspots through time. Reconstructing Australian hotspot paleolatitudes makes use of the global reference frame established by the geocentric axial dipole hypothesis. The classic paleomagnetic approach to establishing paleolatitude typically uses studies of discrete formations of known age, but the nearly continuous record of volcanism over ~34 Ma permit using paleomagnetic data from multiple, different studies that overlap in magnetization age in conjunction. This improves the robustness and precision of our paleolatitude estimates for Eastern Australian hotspot volcanoes. A northward shift of hotspot paleolatitudes between 15-24 Ma of ~300-1010 km (95% confidence limits) is observed for volcanoes along the Comboyne, Canobolas and Tasmantid tracks, and for interpolated positions along the Cosgrove and Lord Howe tracks but is significantly resolved only for volcanoes along Comboyne and Canobolas tracks, as well as for two ages from the Stradbroke and Britannia seamounts on the Tasmantid track. Before 24 Ma most data plot to the North of a fixed present day hotspot location in the paleomagnetic reference but 95% confidence limits overlap with it. Notable exceptions are an age from Hillsborough Volcano (Cosgrove Hotspot), and an age from Horse Head (Lord Howe Hotspot) that lie a small distance to the North 22-743km, and 167-988km North respectively. Importantly, paleolatitude changes observed along eastern Australian tracks are all explainable by the net rotation of the solid Earth, or true polar wander, with hotspots embedded in the global moving hotspot reference frame.